Dust explosions in the process industries - Eckhoff, Rolf K. (Gulf Professional Pub., 2003)
Unfortunately, dust explosions are common and costly in a wide array of industries such as petrochemical, food, paper and pharmaceutical. It is imperative that practical and theoretical knowledge of the origin, development, prevention and mitigation of dust explosions is imparted to the responsible safety manager. The material in this book offers an up to date evaluation of prevalent activities, testing methods, design measures and safe operating techniques. Also provided is a detailed and comprehensive critique of all the significant phases relating to the hazard and control of a dust explosion. An invaluable reference work for industry, safety consultants and students. * A completely new chapter on design of electrical equipment to be used in areas containing combustible/explosible dust * A substantially extended and re-organized final review chapter, containing nearly 400 new literature references from the years 1997-2002 * Extensive cross-referencing from the original chapters 1-7 to the corresponding sections of the expanded review chapter.
Keywords: Dust explosions.; Fire prevention.; Industrial accidents.; elektronické knihy; electronic books